Chapter 5 - Transport, fate, and bioavailability of emerging pollutants in soil, sediment, and wastewater treatment plants: potential environmental impacts - Chacón Jiménez, Luz María (2022)
Emerging contaminants (ECs) are chemicals of natural or synthetic origin that have been recently discovered and are not commonly monitored. These ECs have potential to contaminate the environment and have adverse effects on human health. The term EC refers to a broad spectrum of compounds including pharmaceuticals and personal care products (PPCPs), antimicrobials, animal and human hormones, microplastics, and industrial and domestic detergents. These compounds enter the environment depending on their pattern of use and mode of application. Once released into the environment, they undergo different degradation processes. Their transformation, mobilization, bioavailability and persistence in soil, sediments, or wastewater remain relatively unresolved. Some critical aspects to understand their fate in nature are the molecular structure of each compound and some environmental conditions such as temperature, nutrient availability, and irradiation. ECs are currently increasingly being detected in different environments with unpredictable consequences for these ecosystems and/or human health. In this chapter, the transport of emerging pollutants, the fate and bioavailability of ECs, and potential environmental impacts will be described. The main focus will be on PPCPs, antimicrobials, and industrial and domestic detergents.